Turn Holding Cues in Multi-participant Conversations in Downton Abbey Te - Sudartinah, Titik; Nursanti, Emi (Lingua Cultura, 2018)
This study aimed to identify the turn-holding cues in Downton Abbey television series and describe the factors contributing to the effective use of them. This study used a descriptive qualitative method. The data were multi-participant conversations in the television series, specifically the first three episodes of the first season. The procedures for conducting the study were collecting the data, completing them with their context, setting, and then analyzing them. The result shows that to hold a turn, speakers use cues such as filled pause, verbal filler, tactically placed silent pause, new start, grammatical incompleteness, and rush-through. The speakers’ attempt to hold the turn are successfully accomplished as they can continue finishing their utterances without any interruption from other participants. The factors contributing to the effective use of turn-holding cues are putting the cues at strategic places, and most importantly, cooperation among participants.